Prática docente na Educação Ambiental nas escolas públicas de Humaitá - AM - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The worldwide concern with the effects arising from the environmental issue has generated successive conferences to discuss the problems that affect the planet. With that, we have Environmental Education as a pedagogical means to work on themes related to the environmental issue, having the possibility of being developed in multiple spaces, including the school environment. Considering that this action is currently necessary as a result of the worsening that occurs in all regions of Brazil, specifically in the Amazon region, with the growth of fire rates, deforestation, increase in areas for agriculture and livestock, invasions of indigenous lands, among others, putting at risk all the ecosystems that are present in the region, as they suffer interference from all the environmentally degrading aspects. Thus, the general objective of this dissertation was to identify the pedagogical practices of environmental education in regular subjects in the final grades of Elementary School II (6th to 9th grade) in schools in the urban area of the municipality of Humaitá-AM. Thirteen civil servants from two state schools participated in the event, ten teachers, two pedagogues and one manager. The research is qualitative, and used the following procedures: bibliographical and documentary research. The instrument for data collection was the semi-structured virtual questionnaire through google forms and for data reading, content analysis was use. The results obtained demonstrate that the teaching participants are deployed to include environmental education activities in their practice; situations appeared in which the information is still fragmented even for them, generating some confusion about who should carry out the activities. They reported that to develop the activities, they face several difficulties, such as lack of interest from the students and those responsible to encourage the students to participate. It was found that the conservationist macro-trend of Environmental Education still predominates. Thus, the fragmentation of the theme in the school environment hinders a more critical understanding of the socio-environmental theme. It is important to know the limitations that exist in carrying out activities in the school environment, aiming to visualize the possibilities of change towards a critical environmental education. Moments for exchanging experiences should be valued, establishing dialogues between the various actors that affect and are affected by environmental damage, such as the destination of solid waste, which is so worked on in the school environment, but is difficult to resolve. In Brazilian education, it is necessary to break paradigms and think of the educational process as everyone's duty. Education is not only made with the figure of the teacher and the student, as many evidence, behind a school there is a considerable number of servers in other functions that contribute to the development of the educational process, as well as the external community. It is necessary to call these professionals and individuals to work in partnership with teachers in the development of projects and strategies to provide critical environmental education.
Keywords: Educação ambiental - Humaitá (AM); Educação ambiental - Estudo e ensino; CIENCIAS HUMANAS: EDUCACAO; Educação Ambiental; Prática Pedagógica; Ambiente Escolar; Profissionais de Educação; Ensino